Examining metrics and magnitudes of molecular genetic differentiation used to delimit cetacean subspecies based on mitochondrial DNA control region sequences. (June 2017) - Rosel, Patricia E.; Hancock‐hanser, Brittany L.; Archer, Frederick I.; Robertson, Kelly M.; Martien, Karen K.; Leslie, Matthew S.; Berta, Annalisa; Cipriano, Frank; Viricel, Amelia; Viaud‐Martinez, Karine A.; Taylor, Barbara L.
Abstract: Cetacean taxonomy continues to be in flux and molecular genetic analyses examining alpha taxonomy in cetaceans have relied heavily on the mitochondrial DNA control region. However, there has been little consistency across studies; a variety of metrics and levels of divergence have been invoked when delimiting new cetacean species and subspecies. Using control region sequences, we explored, across pairs of well‐recognized cetacean populations, subspecies, and species, a suite of metrics measuring molecular genetic differentiation to examine which metrics best categorize these taxonomic units. Nei's estimate of net divergence ( d A ) and percent diagnosability performed best. All but a single, recently diverged species were unambiguously identified using these metrics. Many subspecies were found at intermediate values as expected, allowing separation from both populations and species, but several had levels of divergence equivalent to populations, resulting in underclassification errors using this single marker. Coupling d A with additional measures, such as percent diagnosability, examining appropriate nuclear genetic markers, and interpreting results in a broader biological context will improve taxonomic investigations in cetaceans.